1999
DOI: 10.1007/s11661-999-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grain size on the constitutive response and substructure evolution of MONEL 400

Abstract: The influence of grain size on the constitutive behavior (strain-rate and temperature dependence of the yield stress and strain hardening) and substructure evolution of MONEL 400 was investigated. Increasing the grain size from 9.5 to 202 m was seen to reduce the quasi-static yield strength from 290 to 115 MPa, while having a minimal effect on the work-hardening response. Increasing the strain rate from quasi-static to dynamic strain rates (3000 s Ϫ1 ) was seen to increase the yield and overall flow-stress lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 33 publications
7
44
1
Order By: Relevance
“…Mecking [68] developed the conceptual linkage of the various regions within a polycrystalline aggregate and there is a considerable experimental support for his concepts. Recently, Gray et al [69] observed a higher dislocation density in the grain-boundary regions of plastically deformed brass, supporting the ideas discussed here. Meyers and Ashworth [68] considered the polycrystalline aggregate as a composite comprised of a grain interior with flow stress s fG , and the grain boundary regions with flow stress s fGB .…”
Section: Analytical Modelingsupporting
confidence: 88%
See 1 more Smart Citation
“…Mecking [68] developed the conceptual linkage of the various regions within a polycrystalline aggregate and there is a considerable experimental support for his concepts. Recently, Gray et al [69] observed a higher dislocation density in the grain-boundary regions of plastically deformed brass, supporting the ideas discussed here. Meyers and Ashworth [68] considered the polycrystalline aggregate as a composite comprised of a grain interior with flow stress s fG , and the grain boundary regions with flow stress s fGB .…”
Section: Analytical Modelingsupporting
confidence: 88%
“…Nevertheless, there are other effects of great importance. Four principal factors contribute to grainboundary strengthening: (a) the grain boundaries act as barriers to plastic flow (the original pile-up mechanism [57][58][59][60]); (b) the grain boundaries act as dislocation sources [61]; (c) elastic anisotropy causes additional stresses in grain-boundary surroundings [65,66]; and (d) multislip is activated in the grain-boundary regions, whereas grain interiors are initially dominated by single slip, if properly oriented [64][65][66]69]. As a result, the regions adjoining grain boundaries harden at a rate much higher than grain interiors.…”
Section: Grain Size Effectsmentioning
confidence: 99%
“…The observation that the measured reload yield strength of the sample prestrained at 7 GPa lies initially below the equivalent-strain low-rate flow stress may additionally reflect a small kinematic hardening, Bauschinger effect [43], on the post-shock mechanical response. Overall, the lack of an enhanced-shock-hardening response in the Ti stresses to 5 GPa is thought to be fully consistent with the previously discussed dominant role of the Peierls stress limiting dislocation storage during shock prestraining [44]. However, when the peak shock pressure imposed exceeds the a-co phase transition, as in the 11 GPa shock case, then a greatly increased deformation twin density is generated in response to the transformation-induced local shears in the lattice.…”
Section: Shock Recovery Experiments -Mechanical Behaviorsupporting
confidence: 84%
“…Since the grain size [14] also plays a role in mechanical property dependence, work hardening and strain rate effects on grain boundaries in Alloy 400 should be evaluated. The purchase specification for manufacture of this material should speci~the smallest grain size possible to obtain the minimum mechanical and weldability properties.…”
Section: )mentioning
confidence: 99%